Comparative analysis of the efficiency of transportation corridors in Mongolia (Mongolian Journal of Geography and Geoecology, 2025)
The development of transportation corridors is especially important for landlocked countries, as it enhances their capacity to connect internal regions with seaports, markets, and production centers. Within the framework of the Regional Development Concept of Mongolia (2024-2050), vertical and horizontal transportation corridors of transport infrastructure have been identified. For these transportation corridors, it is important to establish the development priority based on a comparative analysis of the efficiency of the regional transport network, and then determine the distribution of construction and investment. Therefore, the purpose of this study is to conduct a comparative analysis of the efficiency of the above-mentioned transportation corridors and establish the priority. The Time-Cost-Distance (TCD) method was employed to evaluate each corridor. Data was collected on the current state of transport infrastructure, as well as the time and cost associated with transportation processes along each corridor. Based on the comparative analysis, the corridors were ranked into three priority groups, with Corridor 3 in the first priority, Corridors 1 and 4 in the second priority, and Corridors 2, 5, and 6 in the third priority. Corridor 3, which is included in the first priority, is the main road corridor of Mongolia. Corridors 1 and 4, which are included in the second priority, are important for the integration of Central and Eastern Asia into regional economic cooperation and demonstrate the importance of developing them first. Corridors 2, 5, and 6, which are included in the third priority, have relatively low economic efficiency compared to other corridors, so they can be developed at a later stage.